APLIKASI HIJAUAN DAN KOMPOS Mucuna bracteata PADA TANAMAN SAWI HIJAU (Brassica juncea L.) - Ririn Safitry; Hapsoh Hapsoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study was conducted to determine the effect of forage and Mucuna bracteata compost on increasing production of green mustard plant (Brassica juncea L.). This research has been conducted in the experimental garden of Faculty of Agriculture, University of Riau, Jalan Bina Widya, Baru Simpang Village, District Tampan, Pekanbaru. This research was carried out for 2 months from the month of June-July 2016. The study was conducted experimentally using a completely randomized design (CRD), which consists of 5 treatments and 4 replications. The treatments used are as follows: 0 ton / ha, 5 ton / ha forage, 10 tons / ha of forage, 5 ton / ha of compost, 10 tons / ha of compost. The parameters observed, plant height, leaf number, root volume, root fresh weight, fresh weight canopy, canopy ratio roots. Forage Mucuna bracteata tends to increase the average value of the observations of mustard greens, but not increase production of mustard greens. Compost Mucuna bracteata able to increase crop production green cabbage all parameters of observation. Dose Mucuna bracteata best compost 10 tons / ha which enhances growth of green cabbage (Brassica juncea L.) Yield of 1.81 kg per plot equivalent to 12.56 tonnes / ha (34.47%), compared with no treatment. Keywords: hijauan, kompos, Mucuna bracteata, sawi hijau.